TRENDS AND PROBLEMS OF INNOVATIVE ACTIVITIES DEVELOPMENT OF DOMESTIC INDUSTRIAL ENTERPRISES - Oksana Prodius (Green, Blue and Digital Economy Journal, 2020)
The aim of the article is to study the dynamics of innovations development, to identify the main problems of innovative activities development and to advance proposals for the incentive instruments formation. The main method of research is the systemic and structural approach, which makes it possible to organize the search for solving problems most effectively. Methods of comparative, functional analysis and classification are also used. The theoretical basis of the article is the conceptual provisions and scientific principles developed by domestic and foreign scientists on the innovative development of industrial enterprises, tools for their implementation. However, the problems associated with the development and implementation of an effective mechanism for applying the innovative development of industrial enterprises in the context of the need to intensify the inclusiveness of innovative processes remain unfinished. The importance and significance of these questions determined the choice of the topic of the article, setting of the purpose and objectives of the study. The article analyzes the status and dynamics of innovative activities of domestic enterprises. The main trends and problems of the enterprises’ innovative development in modern conditions of limited financing and reducing the foreign investment resources are revealed. The level of using various types of innovations by industrial enterprises is investigated and the peculiarities of cost sharing for innovative activities are determined. The condition analysis of innovative activities of Ukraine’s industrial enterprises is carried out, namely the ratio of innovative products sold, the ratio of enterprises engaged in innovative activities, the number of new technological processes introduction and the production development of new types of products by industrial enterprises, funding sources of innovative activities. The structural analysis of various instruments efficiency of innovations financing in the domestic market is carried out. Ukraine’s innovation infrastructure should be provided with adequate resources in the context of a modern international methodology to support innovative business, which will help to minimize and close this gap. The available resources and potential should be focused on supporting research, which is one of the foundations of innovation potential, and creating an effective infrastructure that will help to transform research results into a product suitable for commercialization. Programs should be introduced to support academic payouts, start-ups, or other means of commercial use of innovative investments. The exposure-response relationships of innovative development stagnation are revealed and the ways of optimization and elimination of imbalance are provided. The recommendations for improving the innovative activities of industrial enterprises are developed.